Pengaruh Sistem Informasi Akuntansi terhadap Kinerja Usaha Mikro Kecil (UMK) di Kecamatan Kabanjahe - Sinulingga, Yosi Delmy Ocha Br; Siahaan, Audrey M.; Siboro, Danri Toni (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
This research aims to find out what influence accounting information systems have on the performance of Micro and Small Enterprises in Kabanjahe District. The independent variable is the accounting information system, and the dependent variable is performance. The research method used is primary data collection techniques in the form of questionnaires. The sampling method used in this research was Conveience Sampling, with a total sample of 40 respondents. Data processing uses SPSS version 26 tools. Tests used in this research include descriptive statistical analysis, validity and reliability tests, normality tests, simple linear regression, and partial significance tests (t tests). The results of this research show that the Accounting Information System (X) has a positive, significant effect on the performance (Y) of Micro and Small Businesses in Kabanjahe sub-district. Based on the results of the t test, the accounting information system variable has an effect on the performance of micro and small businesses in Kabanjahe sub-district by 0.001 (0.001<0.05).